Reduced plasma levels of microtubule-associated STOP/MAP6 protein in autistic patients. (30th November 2016) - Wei, Hongen; Sun, Shibang; Li, Yonghong; Yu, Shunying
Abstract: Autism is a neurodevelopmental disorder characterized by abnormal reciprocal social interactions, communication deficits and repetitive behaviors with restricted interests. A previous quantitative proteomic profiling study demonstrated that microtubule-associated stable tubule only polypeptide (STOP; also known as MAP6) protein was significant reduced in the cerebral cortex from BTBR mouse model of autism compared to the C57BL/6J mice. In the present study, the result showed that the concentration of STOP/MAP6 protein was significantly reduced in the plasma of autistic subjects than that in healthy controls. Finally, a possible mechanism of STOP/MAP6 protein in the pathogenesis of autism was proposed. Highlights: The widely accepted biomarkers for autism are still lacking. The level of STOP/MAP6 protein was reduced in the plasma of autistic subjects. A possible mechanism of STOP/MAP6 in the pathogenesis of autism was proposed.